Art-projective Diagnostics in Training – the Possibility of Personal Development and Self-cognition (Journal of Educational Sciences, 2018)
The article considers the possibilities of art-projective diagnostics in trainings, which are relevant in modern psychological and pedagogical practice. In recent years, the format of the training has changedsuccessively from working with children and adults, with increasing opportunities for reflection, personal development and self-cognition. Psychological and art-therapeutic approaches, phototherapy are applied. The article emphasizes the use of storytelling and the ability of the coach to create an atmosphere of trust during the training. The article reveals the wealth of methods and techniques for discovering,developing creativity and interacting with children and adolescents. An example of designing a training with art-diagnostics is given. The structure of the training includes: 1. Setting / rapport / trust. 2. Warmingup activity 3. Update of visual, audial and kinesthetic sensations. 4. Individual artwork- the development of the theme. 5. Active verbalization and nonverbal presentation. 6. Teamwork. 7. The final stage,self-reflection.Key words: art therapy, art diagnostics, visual sociology, phototherapy, training, personal development, self-cognition.